2014
DOI: 10.1091/mbc.e13-08-0453
|View full text |Cite
|
Sign up to set email alerts
|

Nel positively regulates the genesis of retinal ganglion cells by promoting their differentiation and survival during development

Abstract: Nel is a thrombospondin-1–like extracellular glycoprotein that is predominantly expressed in the vertebrate nervous system. It stimulates the genesis of retinal ganglion cells (RGCs) by promoting their differentiation and survival during development and is essential for production of proper numbers of RGCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 59 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…Nel ‐like2 is predominantly expressed in the nervous system and has been implicated in neural development . Recently, we showed that chicken Nel (NELL2) regulates retinal axon guidance and production of retinal ganglion cells during development …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nel ‐like2 is predominantly expressed in the nervous system and has been implicated in neural development . Recently, we showed that chicken Nel (NELL2) regulates retinal axon guidance and production of retinal ganglion cells during development …”
mentioning
confidence: 99%
“…Recently, we showed that chicken Nel (NELL2) regulates retinal axon guidance (15) and production of retinal ganglion cells during development. (16) Expression of NELL1 and NELL2 genes has been studied in human lymphoma, in cancers of the central nervous system, prostate, and bladder, and in cancer cell lines. (17)(18)(19)(20) Furthermore, NELL1 and NELL2 expression was reported in adult and embryonic normal kidney.…”
mentioning
confidence: 99%
“…Therefore it seems unlikely that Robo receptors are responsible for the Nell2-medicated eye-specific retinogeniculate projection. In addition, whereas EGF-like repeats of the Nell2 protein appear to be responsible for repulsion of spinal commissural axons (Jaworski et al, 2015), our previous studies have revealed that cysteinerich domains exert inhibition of retinal axons (Nakamoto et al, 2014). These findings suggest that Nell2 regulates behaviour of retinal and spinal commissural axons through its different domains binding to distinct cognate receptors.…”
Section: Discussionmentioning
confidence: 90%
“…It has been previously reported that Nell2 is expressed in developing RGCs (Nakamoto et al, 2014;Nelson et al, 2002;Wang et al, 2007). It is possible that Nell2 is expressed specifically in contra-or ipsi-laterally projecting RGCs and is involved in specification of their laterality of projection.…”
Section: Nell Null Mice Show No Obvious Defects In Rgc Axon Pathfindingmentioning
confidence: 98%
See 1 more Smart Citation